Inibição da divisão celular em Xanthomonas citri subsp. citri e Bacillus subtilis - Silva, Isabel Cristiane da [UNESP] (2014)
The bacterium Xanthomonas citri subsp. citri (Xac) is the causal agent of asiatic citrus canker, a severe disease that affects all the cultivars of citrus in the main citrus producing areas worldwide. There is no curative treatment for citrus canker. Thus, the eradication of infected plants constitutes the only effective control for the spread of disease. Since the eradication program is under threat, and with a clear risk of Xac becoming endemic in the main orange producing area worldwide, there is an urgent need for the development of new strategies to fight citrus canker. In this work, were evaluated the potential use of alkyl galates to prevent Xac growth. These esters displayed a potent anti-Xac activity similar to kanamycin (positive control) as observed by the Resazurin Microtiter Assay (REMA). Treatment of Xac with these compounds induced altered cell morphology, and investigation of the possible intracellular targets using Xac strains labeled for septum and centromere pointed to a common target involved with chromosome segregation and cell division. Furthermore, artificial inoculation of citrus with Xac pre-treated with alkyl galates showed that the bacterium loses the ability to colonize its host, which argued in favor of the potential of these esters to protect citrus plants against Xac infection. In attempt to determine their mechanism of action some experiments were performed in Bacillus subtillis. Alkyl gallates were also active against B. subtilis and the FtsZ localization is rapidly perturbed after the treatment, which suggested that the compounds may target the cell division machinery. When studied in vitro, the alkyl gallates affected FtsZ by forming structures that could easily be spun down at high velocity, independent of the presence of nucleotide. These structures seem to be specific since the BSA (bovine serum albumin) protein did not sediment in the presence of the alkyl gallates. Also, GTP hydrolysis, an indicator ...